Communicating change – meaningful moments, situated cognition and music therapy: A response to North (2014). (November 2014) - Fachner, Jörg
How can we document and explain changes in, and outcomes of, music therapeutic work? In therapy, change is connected to a timeline of meaningful moments of insight and communication between therapist and client, which need to be understood through a situationist stance on musical experience. Social neuroscience research that describes time processes of musical communication and physiological change creates frameworks for researching such processes. What accounts for change in music therapy can be elucidated by recent research into music therapy praxis of improvising and verbal reflection and research on music's effects on neural processing, particularly in fronto-temporal and right-hemisphere regions that are implicated in music, language and emotion processing.